Vanadium silicocarbide film, vanadium silicocarbide film-coated member, and method for producing vanadium silicocarbide film-coated member
By controlling the element concentrations of vanadium, silicon and carbon in the vanadium base film, a vanadium silicate carbosilicide film with a low friction coefficient is solved, and the problem of insufficient friction coefficient of vanadium silicate carbosilicide film in the prior art is suitable for pressing and forging processing in semi-dry or dry environments.
Patent Information
- Application Number
- JP2020163022
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-29
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2040-09-29
AI Technical Summary
In the prior art, although there is a high wear resistance vanadium silicate carbosilicide film, its friction coefficient still needs to be further improved to meet the requirements of environmental protection, reduce the use of lubricant during friction, or to press and forge in a semi-dry or dry environment.
By controlling the element concentrations of vanadium (V), silicon (Si) and carbon (C) in the vanadium-based film, the total concentration reaches 90 at% or above, and satisfying a specific element concentration range (vanadium 8-30 at%, silicon 8-30 at%, carbon 40-80 at%), a vanadium silicate carbon-silicide film with a low friction coefficient is formed.
It realizes the formation of a film with a low friction coefficient during pressing and forging, reducing the use of lubricating oil during friction, and is suitable for processing in semi-dry or dry environments.
Smart Images

Figure 0007667645000005 
Figure 0007667645000006 
Figure 0007667645000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a vanadium silicocarbide film, a vanadium silicocarbide film-coated member, and a method for producing a vanadium silicocarbide film-coated member. [Background technology]
[0002] Conventionally, a vanadium-based film having excellent lubricity is formed on the surface of a die used in press working or forging to prevent wear of the die surface and damage to the workpiece caused by contact friction during processing of the workpiece. As such a vanadium-based film, Patent Document 1 discloses that a vanadium silicon carbonitride film containing vanadium, silicon, carbon, and nitrogen is coated on the surface of a steel material by using a plasma chemical vapor deposition method. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-035108 A Summary of the Invention [Problem to be solved by the invention]
[0004] Recently, from the viewpoint of environmental protection, for example, in press working or forging of a workpiece using a die, it is required to reduce the amount of lubricant used or to perform the workpiece in a so-called semi-dry or dry environment without using lubricant. In order to enable press working or forging in such an environment, it is desired to form a film with a lower friction coefficient on the die surface. However, although the vanadium silicon carbonitride film described in Patent Document 1 has excellent wear resistance, there is room for improvement in terms of the friction coefficient.
[0005] The present invention has been made in view of the above circumstances, and has an object to provide a vanadium-based film having a low friction coefficient. [Means for solving the problem]
[0006] The present inventors discovered that in a vanadium-based film containing vanadium (V), silicon (Si) and carbon (C), the friction coefficient of the vanadium-based film is low when the sum of the vanadium element concentration [at %], silicon element concentration [at %] and carbon element concentration [at %] in the film satisfies a predetermined numerical range, and thus completed the present invention.
[0007] Aspects of the present invention that solve the above problems are listed below. [1] Contains vanadium, silicon, and carbon; The total of the vanadium element concentration, the silicon element concentration, and the carbon element concentration in the film is 90 at% or more. the law of nature, The vanadium element concentration in the film is 8 to 30 at%, the silicon element concentration is 8 to 30 at%, and the carbon element concentration is 40 to 80 at%, Vanadium silicocarbide film 。 [2 The vanadium element concentration, the silicon element concentration, and the carbon element concentration in the film satisfy the following formula (1): ] The vanadium silicocarbide film described. (carbon concentration – vanadium concentration – silicon concentration) ≧ 10.0 at% (1) [ 3 ]Hardness is 2700HV or more.[1] or [2] The vanadium silicocarbide film according to claim 1. [ 4 ] a substrate, and [1] to [ 3 and the vanadium silicocarbide film according to any one of claims 1 to 4. [ 5 ]the above[ 4 ], comprising: supplying vanadium chloride gas, a silicon source gas, a carbon source gas, and a hydrogen gas into a chamber; and forming a vanadium silicocarbide film on a substrate by using a plasma chemical vapor deposition method to produce the vanadium silicocarbide film-coated member. [ 6 In the vanadium silicocarbide film formation process, a pulse voltage is applied by using a pulse power source with a duty ratio, which is the voltage application time per pulse cycle, set to 5 to 60%.5 4. A method for producing a vanadium silicocarbide film-coated member according to claim 3. [ 7 In a vanadium silicocarbide film forming process, the vanadium chloride gas, the silicon source gas, the carbon source gas, the hydrogen gas and the argon gas are supplied into the chamber, a flow rate ratio of the vanadium chloride gas, the silicon source gas, the carbon source gas, the hydrogen gas, and the argon gas is 1:0.25-2:3-20:20-35:0.5-2; 5 ]or[ 6 4. A method for producing a vanadium silicocarbide film-coated member according to claim 3. [ 8 ] the silicon source gas is an organosilane gas; 5 ]~[ 7 13. The method for producing a vanadium silicocarbide film-coated member according to any one of claims 1 to 12. [ 9 ]The organosilane gas is monomethylsilane gas, [ 8 4. A method for producing a vanadium silicocarbide film-coated member according to claim 3. Effect of the Invention
[0008] According to the present invention, a vanadium silicocarbide film having a low coefficient of friction can be provided. [Brief description of the drawings]
[0009] [Figure 1] 1 is a diagram showing a schematic configuration of a vanadium silicocarbide film-coated member according to an embodiment of the present invention. [Diagram 2] 1 is a diagram showing a schematic configuration of a film forming apparatus for a vanadium silicocarbide film according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram showing the shape of a test piece. [Figure 4] FIG. 1 is a schematic diagram of a ball-on-disk test. [Diagram 5] FIG. 1 shows an X-ray diffraction spectrum of a vanadium silicate carbide film (VSiC). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In this specification and the drawings, elements having substantially the same functional configuration are designated by the same reference numerals, and redundant description will be omitted.
[0011] (Vanadium silicocarbide film-coated components) 1 is a diagram showing a schematic configuration of a vanadium silicocarbide film-coated member 1 of this embodiment. The vanadium silicocarbide film-coated member 1 of this embodiment is composed of a substrate 2 and a vanadium silicocarbide film 3 formed on the substrate 2. The vanadium silicocarbide film-coated member 1 is used as various tools and parts, such as cutting tools, gear cutting tools, forging tools, and automobile parts, in addition to dies used for press working and forging.
[0012] The type of the substrate 2 is not particularly limited, and a material suitable for the application of the vanadium silicocarbide film-coated member 1 is used. For example, various steel materials such as so-called cold work tool steels such as SKD11, DC53, or SKH51, cold work die steels (cold work die steels), or high speed tool steels (high speed steels) can be used as materials for the substrate 2 such as dies and tools.
[0013] (Vanadium silicocarbide film) The vanadium silicocarbide film 3 of this embodiment contains vanadium (V), silicon (Si), and carbon (C), and is a film in which the total of the vanadium element concentration, silicon element concentration, and carbon element concentration is 90 at% or more. As will be shown in the examples described later, the vanadium silicocarbide film 3 in which the total of the vanadium element concentration, silicon element concentration, and carbon element concentration is 90 at% or more is a film that has a low coefficient of friction with other members that come into contact with it (for example, the material to be molded when the vanadium silicocarbide film-coated member 1 is a die). The "other members that come into contact with it" are not particularly limited, and examples thereof include steel materials in general, such as alloy steel, carbon steel, aluminum alloy materials, magnesium alloy materials, and titanium alloy materials. The reason why the friction coefficient between the vanadium silicocarbide film 3 and other members that come into contact with it is low is believed to be that the vanadium silicocarbide film 3 contains a large amount of amorphous silicon carbide (SiC), and therefore an oxide coating is formed on the film surface when the vanadium silicocarbide film 3 slides against other members, resulting in good sliding characteristics.
[0014] The total of the vanadium element concentration, silicon element concentration, and carbon element concentration in the vanadium silicocarbide film 3 is more preferably 93 at% or more. More preferably, it is 95 at% or more. The vanadium silicocarbide film 3 may contain 10 at% or less of nonmetallic elements. Examples of nonmetallic elements include fluorine, argon, chlorine, and hydrogen contained in the raw material gas and argon gas supplied in the vanadium silicocarbide film formation process, and oxygen and nitrogen contained in the gas remaining in the chamber of the film formation device that forms the vanadium silicocarbide film. The nonmetallic elements contained in the vanadium silicocarbide film 3 are more preferably 7 at% or less. More preferably, it is 5 at% or less. The vanadium element concentration, silicon element concentration, and carbon element concentration in the vanadium silicocarbide film 3 can be measured by composition analysis using an EPMA. Furthermore, the X-ray diffraction spectrum of the vanadium silicocarbide film 3 has a vanadium carbide peak, and no peaks of vanadium silicocarbide, silicon carbide, or vanadium silicide were observed. The vanadium silicocarbide film 3 may be an amorphous film, and for example, no peak of vanadium carbide may be observed.
[0015] The vanadium silicocarbide film 3 preferably has a vanadium element concentration of 8 to 30 at%, a silicon element concentration of 8 to 30 at%, and a carbon element concentration of 40 to 80 at%. When the vanadium element concentration is 8 to 30 at%, the vanadium-derived lubricity improvement effect is easily obtained, and the friction coefficient between the vanadium silicocarbide film 3 and other members is easily reduced. When the silicon element concentration is 8 to 30 at%, amorphous silicon carbide (SiC) is easily formed in the vanadium silicocarbide film 3, and when the vanadium silicocarbide film 3 slides against other members, an oxide film is formed on the film surface, and the friction coefficient between the vanadium silicocarbide film 3 and other members is easily reduced. When the carbon element concentration is 40 to 80 at%, amorphous silicon carbide (SiC) and amorphous carbon are easily formed in the vanadium silicocarbide film 3, and the friction coefficient between the vanadium silicocarbide film 3 and other members is easily reduced. The vanadium element concentration is more preferably 9 at% or more. The vanadium element concentration is more preferably 25 at% or less. The silicon element concentration is more preferably 9 at% or more. The silicon element concentration is more preferably 25 at% or less. The carbon element concentration is more preferably 50 at% or more. The carbon element concentration is more preferably 80 at% or less.
[0016] From the viewpoint of further reducing the friction coefficient, it is more preferable that the vanadium element concentration, silicon element concentration, and carbon element concentration in the vanadium silicocarbide film 3 satisfy the following formula (1). (carbon concentration – vanadium concentration – silicon concentration) ≧ 10.0 at% (1)
[0017] By satisfying the above formula (1), the vanadium silicocarbide film 3 contains a large amount of amorphous carbon, which is known to have a low coefficient of friction, and this is thought to result in a lower coefficient of friction for the vanadium silicocarbide film 3. From the viewpoint of further reducing the coefficient of friction, it is more preferable that the vanadium element concentration, silicon element concentration, and carbon element concentration in the vanadium silicocarbide film 3 satisfy the following formula (2). (carbon concentration – vanadium concentration – silicon concentration) ≧ 14.0 at% (2)
[0018] The hardness of the vanadium silicocarbide film 3 is appropriately set according to the application, but is preferably 2700HV or more from the viewpoint of obtaining a film with excellent durability. The hardness of the film in this specification is Vickers hardness. The hardness is measured using a nanoindentation method. Specifically, a Berkovich-type diamond indenter is pressed into a test piece with a maximum pressing load of 3mN, the pressing depth is continuously measured, and the Martens hardness obtained from the measurement data of the pressing depth is converted into Vickers hardness to measure the hardness of the film. The film thickness of the vanadium silicocarbide film 3 is appropriately set according to the application, but for example, when the vanadium silicocarbide film 3 is formed on a base material of a mold, the film thickness is preferably 0.5 to 4 μm. In addition, the vanadium silicocarbide film-coated member 1 may have an intermediate layer such as a vanadium film or a vanadium carbide film between the base material 2 and the vanadium silicocarbide film 3 as necessary.
[0019] Next, a method for producing the vanadium silicate carbide film-coated member 1 will be described.
[0020] In this embodiment, the vanadium silicocarbide film-coated member 1 is manufactured by forming the vanadium silicocarbide film 3 on the substrate 2 by a plasma chemical vapor deposition method in which a raw material gas supplied into a film-forming device is turned into plasma to form a film. 2 A plasma processing apparatus 10 as shown in FIG. 1 is used. The plasma processing apparatus 10 includes a chamber 11 into which the substrate 2 is carried, an anode 12, a cathode 13, and a DC pulse power supply 14 that applies a pulse voltage between the anode 12 and the cathode 13. A gas supply pipe 15 through which each raw material gas is supplied is connected to the upper part of the chamber 11, and a gas exhaust pipe 16 through which the gas in the chamber 11 is exhausted is connected to the lower part of the chamber 11. A vacuum pump (not shown) is provided downstream of the gas exhaust pipe 16. The cathode 13 also serves as a support base for supporting the substrate 2, and the substrate 2 carried into the chamber 11 is placed on the cathode 13. A heater (not shown) is provided inside the chamber 11, and the temperature of the substrate 2 is adjusted by adjusting the atmospheric temperature in the chamber 11 with the heater.
[0021] The configuration of the plasma processing apparatus 10 is not limited to that described in this embodiment. For example, a high-frequency power supply may be used instead of the DC pulse power supply 14, or a shower head (not shown) for supplying a raw material gas may be provided and used as the anode 12. Also, the substrate 2 may be heated only by a glow current without providing a heater. That is, the plasma processing apparatus 10 may have a structure capable of converting the raw material gas supplied into the chamber 11 into plasma and capable of forming the vanadium silicocarbide film 3 on the substrate 2 to produce the vanadium silicocarbide film-coated member 1.
[0022] <Preparation for film formation> The substrate 2 is carried into the chamber 11 and set at a predetermined position. After that, the chamber 11 is evacuated to a vacuum so that the pressure inside the chamber 11 is, for example, 10 Pa or less. At this time, the temperature inside the chamber 11 is approximately room temperature. Next, for example, a heater is operated to bake the substrate 2, and then the heater is turned off and the plasma processing device 10 is left to cool the inside of the chamber 11.
[0023] Next, a small amount of hydrogen gas is supplied into the chamber 11, and the heater is operated again. In this heating step, the temperature of the substrate 2 is raised to a temperature close to the plasma treatment temperature. The pressure inside the chamber 11 is maintained at about 100 Pa, for example.
[0024] <Vanadium silicocarbide film formation process> Next, vanadium chloride gas, silicon source gas, carbon source gas and hydrogen gas are supplied into the chamber 11 as raw material gases for forming the vanadium silicocarbide film 3, and a pulse voltage is applied between the anode 12 and the cathode 13 using the pulse power supply 14. As a result, the raw material gases supplied into the chamber 11 are converted into plasma between the anode 12 and the cathode 13, and the vanadium silicocarbide film 3 is formed on the substrate 2.
[0025] As the vanadium chloride gas, for example, vanadium tetrachloride (VCl4) gas or vanadium oxide trichloride (VOCl3) gas is used. Note that it is preferable to use vanadium tetrachloride gas as the vanadium chloride gas, from the viewpoint that the number of elements constituting the gas is small and it is easy to remove impurities in the vanadium silicocarbide film 3. In addition, vanadium tetrachloride gas is also preferable in that it is easily available, is a liquid at room temperature, and can be easily supplied as a gas.
[0026] As the silicon source gas, for example, a silane-based gas such as monosilane gas, disilane gas, dichlorosilane gas, trichlorosilane gas, silicon tetrachloride gas, silicon tetrafluoride gas, etc. may be used. The gases exemplified here may be supplied alone, or two or more kinds of gases may be mixed and supplied. Among these gases, it is preferable to use silicon tetrachloride (SiCl4) gas, which can easily remove chlorine atoms by hydrogen plasma, is thermally stable, and decomposes only in plasma. In addition, an organosilane gas having a molecular structure in which a hydrocarbon functional group is bonded to silicon may be used as the silicon source gas. Since the organosilane gas has a hydrocarbon functional group, it also functions as a carbon source gas. The organosilane gas is not particularly limited as long as it has a molecular structure in which a hydrocarbon functional group is bonded to silicon, and examples of the organosilane gas include monomethylsilane gas, dimethylsilane gas, trimethylsilane gas, and tetramethylsilane gas.
[0027] As the carbon source gas, for example, a hydrocarbon gas such as methane gas, ethane gas, ethylene gas, or acetylene gas is used. The gases exemplified here may be supplied alone or in a mixture of two or more kinds of gases. A mixed gas of the aforementioned organosilane gas and a carbon source gas may also be used. When such a mixed gas is used, the film formation speed is improved compared to when a carbon source gas is used alone.
[0028] When vanadium chloride gas is contained in the raw material gas supplied in the vanadium silicocarbide film formation process, the vanadium silicocarbide film 3 inevitably contains chlorine as an impurity in the remainder excluding vanadium, silicon, and carbon. Since chlorine easily combines with hydrogen gas, when hydrogen gas is contained in the raw material gas, chlorine generated from the vanadium chloride gas combines with hydrogen and is easily discharged outside the system. This makes it possible to suppress the incorporation of chlorine into the vanadium silicocarbide film 3. Note that the remainder of the vanadium silicocarbide film 3 may contain unavoidable impurities other than chlorine.
[0029] Furthermore, in the vanadium silicocarbide film formation process, when vanadium chloride gas and silicon tetrachloride gas are supplied into chamber 11, the volumetric flow rate of hydrogen gas supplied into chamber 11 is preferably 5 to 25 times the sum of the volumetric flow rates of the vanadium chloride gas and the silicon tetrachloride gas.
[0030] Argon gas may be supplied into the chamber 11 as necessary because argon ions ionize other molecules, thereby contributing to stabilizing the plasma and improving the ion density.
[0031] In the vanadium silicocarbide film forming process, the flow rate ratio of vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas is preferably 1:0.25-2:3-20:20-35:0.5-2. This makes it easier to obtain a vanadium silicocarbide film 3 in which the total of vanadium element concentration, silicon element concentration, and carbon element concentration in the film is 90 at% or more. In this specification, the "flow rate of vanadium chloride gas", "flow rate of silicon source gas", and "flow rate of carbon source gas" used in calculating the above flow rate ratio are the volumetric flow rates of each gas at 0°C and 1 atm supplied into the chamber 11 as a raw material gas for film formation, converted according to the number of vanadium atoms, silicon atoms, and carbon atoms contained in the molecule. For example, since an organosilane gas that can be used as a silicon source gas also functions as a carbon source gas, when calculating the flow rate ratio of a silicon source gas to a carbon source gas when an organosilane gas is used, the volumetric flow rate of the organosilane gas must be counted not only as the flow rate of the silicon source gas but also as the flow rate of the carbon source gas. Therefore, when an organosilane gas is used, the flow rate ratio of a silicon source gas to a carbon source gas is not equal to the volumetric flow rate of the organosilane gas and the volumetric flow rate of a gas (e.g., methane gas) supplied into the chamber 11 as a carbon source gas. Note that, when calculating the above flow rate ratio, the "flow rate of hydrogen gas" refers to the volumetric flow rate of hydrogen gas at 0°C and 1 atm, and the "flow rate of argon gas" refers to the volumetric flow rate at 0°C and 1 atm.
[0032] A specific method of calculating the flow rate when calculating the flow rate ratio is as follows. For example, when vanadium tetrachloride gas having a volumetric flow rate of 3 ml / min at 0° C. and 1 atm is supplied as one of the raw material gases, 1 mol of vanadium tetrachloride contains 1 mol of vanadium, so 3 ml / min is added as the flow rate of vanadium chloride gas when calculating the flow rate ratio. When monomethylsilane gas having a volumetric flow rate of 4.5 ml / min at 0° C. and 1 atm is supplied as one of the raw material gases, 1 mol of silicon and 1 mol of carbon are contained in 1 mol of monomethylsilane, so 4.5 ml / min is added as the flow rate of the silicon source gas and 4.5 ml / min is added as the flow rate of the carbon source gas when calculating the flow rate ratio. When methane gas having a volumetric flow rate of 10 ml / min at 0° C. and 1 atm is supplied as one of the raw material gases, 1 mol of methane contains 1 mol of carbon, so 10 ml / min is added as the flow rate of the carbon source gas when calculating the flow rate ratio. Therefore, when vanadium tetrachloride gas at 3 ml / min, monomethylsilane gas at 4.5 ml / min, and methane gas at 10 ml / min are supplied as raw material gases, the flow rate of vanadium chloride gas when calculating the flow rate ratio is 3 ml / min, the flow rate of silicon source gas is 4.5 ml / min, and the flow rate of carbon source gas is 14.5 ml / min. As another example, consider the case where vanadium tetrachloride gas at 3 ml / min, dimethylsilane gas at 4.5 ml / min, and methane gas at 10 ml / min are supplied. In this case, since 1 mol of silicon and 2 mol of carbon are contained in 1 mol of dimethylsilane, the flow rate of vanadium chloride gas when calculating the flow rate ratio is 3 ml / min, the flow rate of silicon source gas is 4.5 ml / min, and the flow rate of carbon source gas is 19.5 ml / min.
[0033] When monomethylsilane gas and methane gas are used as the source gases supplied into the chamber 11, the ratio of the volumetric flow rates of monomethylsilane gas and methane gas (monomethylsilane gas volumetric flow rate / methane gas volumetric flow rate) is preferably 0.05 to 1.0.
[0034] The pressure in the chamber 11 in the vanadium silicocarbide film forming process is preferably set to, for example, 30 to 200 Pa. The pressure in the chamber 11 is preferably 50 Pa or more, and preferably 150 Pa or less. The power applied in the vanadium silicocarbide film forming process is preferably 150 to 2500 W. When a direct current pulse power supply 14 is used, the power applied in the vanadium silicocarbide film forming process is preferably 150 W, and preferably 1000 W or less. More preferably, it is 600 W or less. The power [W] is a value calculated by voltage [V] x current [A]. The voltage is the set voltage of the pulse power supply 14. The current is a value calculated by (maximum current + minimum current) / 2 in the vanadium silicocarbide film forming process using the current value displayed on the pulse power supply 14. The power can be adjusted by changing the set value of the duty ratio. The duty ratio is defined as the voltage application time per pulse period, and is calculated as Duty ratio (%)=100×Voltage application time (ON time) / {Voltage application time (ON time)+Voltage application stop time (OFF time)}. When a DC pulse power supply 14 is used, the voltage in the vanadium silicocarbide film formation process is preferably 1000 to 2000 V. When a DC pulse power supply 14 is used, the duty ratio in the vanadium silicocarbide film formation process is preferably 5% to 60%. By setting the duty ratio to 5% to 60%, it becomes easier to obtain a vanadium silicocarbide film 3 in which the total of the vanadium element concentration, silicon element concentration, and carbon element concentration is 90 at% or more.
[0035] By using the vanadium silicocarbide film formation process as described above, a vanadium silicocarbide film 3 having a total vanadium element concentration, silicon element concentration, and carbon element concentration of 90 at% or more is formed on the substrate 2, making it possible to produce a vanadium silicocarbide film-coated member 1 having a low friction coefficient.
[0036] Although one embodiment of the present invention has been described above, the present invention is not limited to this example. It is clear that a person skilled in the art can think of various modified or altered examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present invention. EXAMPLES
[0037] A vanadium silicocarbide film was formed on a substrate by plasma enhanced chemical vapor deposition to prepare a test piece of the vanadium silicocarbide film-coated member, and its characteristics were evaluated.
[0038] The substrate on which the vanadium silicocarbide film was formed was a φ22 mm round bar made of DC53, a type of die steel, cut at 6-7 mm intervals and the coating surface of the cut bar mirror-polished as shown in Figure 3. The vanadium silicocarbide film was formed on the mirror-polished side of the substrate. The coating device used had a structure as shown in Figure 2, and the power source was a pulse power supply.
[0039] Example 1 Here, we will explain the manufacturing method of the test piece of Example 1. In the following explanation, the volumetric flow rates of hydrogen gas, argon gas, vanadium tetrachloride gas, silicon tetrachloride gas and methane gas are the volumetric flow rates at 0° C. and 1 atm.
[0040] First, the substrate is placed in the chamber of the deposition device, and the chamber is evacuated for 30 minutes to reduce the pressure inside the chamber to 10 Pa or less. At this time, the heater installed in the chamber is not operated. The atmospheric temperature inside the chamber is measured with a sheathed thermocouple. Next, the heater is set to 200°C, and the substrate is baked for 10 minutes. After that, the heater is turned off, and the deposition device is left for 30 minutes to cool the chamber.
[0041] Next, hydrogen gas is supplied into the chamber at a volumetric flow rate of 100 ml / min, and the exhaust rate is adjusted to set the pressure inside the chamber to 100 Pa. Then, the heater temperature is set to 525° C., and the atmosphere inside the chamber is heated for 30 minutes.
[0042] Next, set the voltage to 800V and the duty ratio to 40%, and operate the DC pulse power supply in unipolar output format. This turns the hydrogen gas into plasma between the electrodes in the chamber. After that, set the volumetric flow rate of the hydrogen gas to 98ml / min, and supply argon gas into the chamber at a volumetric flow rate of 3ml / min. Also, adjust the exhaust rate to set the pressure inside the chamber to 58Pa. Then, increase the voltage of the pulse power supply to 1400V. This turns the hydrogen gas and argon gas into plasma between the electrodes.
[0043] <Vanadium silicocarbide film formation process> Next, the volumetric flow rate of vanadium tetrachloride gas as an example of vanadium chloride gas is set to 3 ml / min, the volumetric flow rate of silicon tetrachloride gas as an example of silicon source gas is set to 4.5 ml / min, the volumetric flow rate of methane gas as an example of carbon source gas is set to 15 ml / min, the volumetric flow rate of hydrogen gas is set to 98 ml / min, and the volumetric flow rate of argon gas is set to 3 ml / min, and each gas is supplied into the chamber. In other words, each gas is supplied so that the flow rate ratio of vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas is 1:1.5:5:33:1. At this time, the exhaust amount is adjusted to set the pressure in the chamber to 58 Pa. Then, the voltage of the pulse power supply is set to 1400 V, and the duty ratio is set to 40%. The power of the pulse power supply at this time is 378 W. As a result, the plasmatized vanadium, silicon, and carbon are adsorbed on the substrate, and a vanadium silicocarbide film containing vanadium, silicon, and carbon is formed on the substrate. This state was maintained for 6 hours to obtain a test piece of the vanadium silicocarbide film-coated member of Example 1 in which the vanadium silicocarbide film was coated on the substrate.
[0044] In Example 2, the duty ratio in the vanadium silicocarbide film formation process was changed to 20%, and the vanadium silicocarbide film was formed under the same conditions as in Example 1, except that the power of the pulse power supply at this time was 266 W.
[0045] In Example 3, the duty ratio in the vanadium silicocarbide film formation process was changed to 10%, and the vanadium silicocarbide film was formed under the same conditions as in Example 1, except that the power of the pulse power supply at this time was 224 W.
[0046] In Example 4, in the vanadium silicocarbide film formation process, the volumetric flow rate of methane gas was changed to 30 ml / min, the volumetric flow rate of hydrogen gas was changed to 83 ml / min, the duty ratio was changed to 10%, and the power of the pulsed power supply at this time was changed to 266 W, and a vanadium silicocarbide film was formed under the same conditions as in Example 1. In the vanadium silicocarbide film formation process of Example 4, each gas is supplied into the chamber with the flow rate ratio of vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas and argon gas being 1:1.5:10:28:1.
[0047] In Example 5, in the vanadium silicocarbide film formation process, the volumetric flow rate of methane gas was changed to 45 ml / min, the volumetric flow rate of hydrogen gas to 68 ml / min, the duty ratio was changed to 10%, and the power of the pulsed power supply at this time was 308 W, and an vanadium silicocarbide film was formed under the same conditions as in Example 1. In the vanadium silicocarbide film formation process of Example 5, the vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas and argon gas were supplied into the chamber in a flow rate ratio of 1:1.5:15:23:1.
[0048] In Example 6, a vanadium silicocarbide film is formed under the same conditions as in Example 1, except that in the vanadium silicocarbide film formation process, the volumetric flow rate of silicon tetrachloride gas is changed to 3 ml / min, the duty ratio is changed to 10%, and the power of the pulsed power supply at this time is 210 W. In the vanadium silicocarbide film formation process of Example 6, each gas is supplied into the chamber with the vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas in a flow rate ratio of 1:1:5:33:1.
[0049] In Example 7, a vanadium silicocarbide film is formed under the same conditions as in Example 1, except that in the vanadium silicocarbide film formation process, the volumetric flow rate of silicon tetrachloride gas is changed to 1.5 ml / min, the duty ratio is changed to 10%, and the power of the pulsed power supply at this time is 224 W. In the vanadium silicocarbide film formation process of Example 7, each gas is supplied into the chamber with the vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas in a flow rate ratio of 1:0.5:5:33:1.
[0050] In Example 8, in the vanadium silicocarbide film formation process, the volumetric flow rates of silicon tetrachloride gas, methane gas, and hydrogen gas were changed to 4.5 ml / min, 25 ml / min, and 88 ml / min, respectively, and the power of the pulsed power supply was 476 W, and an other conditions were the same as in Example 1, except that in the vanadium silicocarbide film formation process of Example 8, the vanadium silicocarbide film was formed under the same conditions as in Example 1, except that the vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas were supplied into the chamber in a flow rate ratio of 1:1.5:8:29:1.
[0051] In Example 9, a vanadium silicocarbide film is formed under the same conditions as in Example 1, except that in the vanadium silicocarbide film formation step, monomethylsilane gas is used as the silicon source gas, the volumetric flow rate of methane gas is changed to 10 ml / min, the treatment time is changed to 3 hours, and the power of the pulsed power supply at this time is 364 W. In the vanadium silicocarbide film formation step of Example 9, each gas is supplied into the chamber with the flow rate ratio of vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas being 1:1.5:4.8:33:1.
[0052] In Example 10, a vanadium silicocarbide film is formed under the same conditions as in Example 1, except that in the vanadium silicocarbide film formation process, monomethylsilane gas is used as the silicon source gas, the volumetric flow rate of methane gas is 30 ml / min, the volumetric flow rate of hydrogen gas is 78 ml / min, the duty ratio is 20%, the treatment time is changed to 3 hours, and the power of the pulse power supply at this time is 241 W. In addition, in the vanadium silicocarbide film formation process of Example 10, each gas is supplied into the chamber with the flow rate ratio of vanadium chloride gas, silicon source gas, carbon source gas, hydrogen gas, and argon gas being 1:1.5:11.5:26:1.
[0053] In Comparative Example 1, a vanadium silicocarbonitride film was formed on a substrate instead of a vanadium silicocarbide film to obtain a test piece of a vanadium silicocarbonitride film-coated member. In the vanadium silicocarbonitride film forming process, the volumetric flow rate of vanadium tetrachloride gas was 5 ml / min, the volumetric flow rate of monomethylsilane (SiH3CH3) gas was 5 ml / min, the volumetric flow rate of nitrogen gas was 50 ml / min, the volumetric flow rate of hydrogen gas was 200 ml / min, the volumetric flow rate of argon gas was 5 ml / min, the voltage of the pulsed power supply was set to 1500 V, the duty ratio was set to 30%, and the power of the pulsed power supply at this time was 285 W. A vanadium silicocarbonitride film was formed on a substrate by a plasma chemical vapor deposition method under these conditions.
[0054] The film formation conditions in the vanadium silicocarbide film formation step in Examples 1 to 10 are summarized in Table 1 below. The film formation conditions in the vanadium silicocarbide nitride film formation step in Comparative Example 1 are summarized in Table 2 below.
[0055] [Table 1]
[0056] [Table 2]
[0057] The vanadium silicocarbide film or vanadium siliconitride film was subjected to thickness measurement, composition analysis, and friction coefficient measurement by ball-on-disk test for the test pieces of Examples 1 to 10 and Comparative Example 1. In addition, Example 1 was subjected to X-ray diffraction analysis.
[0058] (film thickness measurement) The film thickness of the vanadium silicocarbide film or vanadium siliconitride film formed on the substrate was measured by cutting the test piece vertically, mirror-polishing the cut surface, observing the cut surface under a metallurgical microscope at a magnification of 1000 times, and making calculations based on the observed image information.
[0059] (composition analysis) The analysis conditions are as follows. Measuring device: EPMA (JXA-8530F manufactured by JEOL Ltd.) Measurement mode: Semi-quantitative analysis Acceleration voltage: 15 kV Irradiation current: 1.0×10 -7 A Beam Shape: Spot Beam diameter setting value: 0 Spectroscopic crystal: LDE6H, TAP, LDE5H, PETH, LIFH, LDE1H In addition, when the film thickness is 1 μm or less, the EPMA measurement results include the influence of the component composition of the substrate. Therefore, when calculating the composition analysis of a thin vanadium silicocarbide film or vanadium silicocarbonitride film, it is necessary to perform an EPMA measurement of only the substrate in advance, and subtract the vanadium element concentration, silicon element concentration, carbon element concentration, nitrogen element concentration, and chlorine element concentration derived from the substrate from the EPMA measurement results after the formation of the vanadium silicocarbide film or vanadium silicocarbonitride film.
[0060] (Coefficient of friction) The ball-on-disc tester used was a "Tribometer" manufactured by CSM Instruments. The discs were the test pieces of Examples 1 to 10 or the test piece of Comparative Example 1. A ball made of carbon steel S45C and having a diameter of 6 mm was used as the ball to be in contact with the disc. As shown in FIG. 4, the ball was brought into contact with the disc under an environment of 23 to 24°C and 21% humidity, and the disc was rotated so that the sliding speed was 0.167 m / s while applying a load of 5 N to the ball. The contact point between the ball and the disc was a point with a radius of 6 mm from the center of the disc. The friction coefficient between the disc and the ball when the sliding distance between the disc and the ball reached 40 m was taken as the measured value of the friction coefficient of the vanadium silicocarbide film or vanadium silicocarbonitride film formed on the substrate.
[0061] (Film hardness measurement) FISCHER made by Fischer Instruments The nanoindentation method is carried out using SCOPE (registered trademark) H100C. Specifically, a Berkovich-type diamond indenter is pressed into the test piece with a maximum pressing load of 3 mN, and the pressing depth is continuously measured. From the measurement data of the pressing depth obtained, the Martens hardness and the Vickers hardness converted from the Martens hardness are calculated using Fisher Instruments' software "Product name: WIN-HCU (registered trademark)". The calculated Vickers hardness is displayed on the screen of the measuring device, and this value is treated as the hardness of the film at the measurement point. In this example, the Vickers hardness of any 20 points on the outermost surface of each test piece is obtained, and the average value of the obtained hardness is taken as the Vickers hardness of the film.
[0062] The measurement results of the film thickness, film formation rate, composition, friction coefficient and hardness of the vanadium silicocarbide film are shown in Table 3. The measurement results of the film thickness, composition, friction coefficient and hardness of the vanadium silicocarbonitride film are shown in Table 4.
[0063] [Table 3]
[0064] [Table 4]
[0065] As shown in Tables 3 and 4, the friction coefficients of the vanadium silicocarbide films of Examples 1 to 10 are significantly smaller than that of the vanadium siliconitride film of Comparative Example 1. The results of this example show that vanadium silicocarbide films in which the sum of the vanadium element concentration [at%], silicon element concentration [at%], and carbon element concentration [at%] in the film is 90 at% or more have a low friction coefficient.
[0066] Furthermore, as shown in Table 3, the film formation rates in Examples 9 to 10 are at least 1.4 times faster than those in Examples 1 to 8, and the film formation rate is significantly improved. The silicon source gas used in Examples 1 to 8 and Examples 9 to 10 is different from each other. In Examples 1 to 8, silicon tetrachloride gas is used as the silicon source gas, whereas in Examples 9 to 10, monomethylsilane gas is used as the silicon source gas. In other words, in Examples 9 to 10, a mixed gas of monomethylsilane gas and methane gas is supplied into the chamber, and it can be said that the supply of such a mixed gas contributes to the film formation rate. According to the results of this example, the silicon Carbonization It can be seen that the film formation rate can be improved by using a mixture of monomethylsilane gas and a carbon source gas in the vanadium film formation process.
[0067] (X-ray diffraction analysis) Using an XRD analyzer (SmartLab manufactured by Rigaku), an X-ray diffraction analysis was carried out on the surface of the test piece at the end of the formation of the vanadium silicocarbide film of Example 1. In order to obtain information only on the vicinity of the surface of the test piece, the analysis was carried out by the oblique incidence method, the incidence angle was set to 1.0°, and CuKα radiation was used as the X-ray source. The XRD analysis result of Example 1 is shown in Figure 5. As shown in Figure 5, a vanadium carbide (VC) peak was observed in the vanadium silicocarbide film. [Industrial Applicability]
[0068] The vanadium silicocarbide film having a low friction coefficient and the vanadium silicocarbide film-coated member having a vanadium silicocarbide film formed on a substrate according to the present invention can be used in dies, cutting tools, gear cutting tools, forging tools, automobile parts, etc. [Explanation of symbols]
[0069] 1 Vanadium silicocarbide film-coated components 2 Base material 3 Vanadium silicocarbide film 10 Plasma treatment device 11. Chamber 12 Anode 13 Cathode 14 Pulse power supply 15 Gas supply pipe 16 Gas exhaust pipe
Claims
1. Contains vanadium, silicon, and carbon, the total of the vanadium element concentration, the silicon element concentration, and the carbon element concentration in the film is 90 at % or more; A vanadium silicocarbide film, the vanadium element concentration in the film being 8 to 30 at %, a silicon element concentration being 8 to 30 at %, and a carbon element concentration being 40 to 80 at %.
2. 2. The vanadium silicocarbide film according to claim 1, wherein the vanadium element concentration, the silicon element concentration, and the carbon element concentration in the film satisfy the following formula (1): (carbon element concentration−vanadium element concentration−silicon element concentration)≧10.0 at% (1)
3. 3. The vanadium silicocarbide film according to claim 1, having a hardness of 2700 HV or more.
4. A substrate; A vanadium silicocarbide film-coated member comprising: the vanadium silicocarbide film according to any one of claims 1 to 3 formed on the substrate.
5. A method for producing the vanadium silicocarbide film-coated member according to claim 4, comprising the steps of: A method for producing a vanadium silicocarbide film-coated member, comprising: supplying vanadium chloride gas, a silicon source gas, a carbon source gas, and a hydrogen gas into a chamber; and forming a vanadium silicocarbide film on a substrate by using a plasma chemical vapor deposition method to produce the vanadium silicocarbide film-coated member.
6. 6. The method for producing a vanadium silicocarbide film-coated member according to claim 5, wherein in the vanadium silicocarbide film forming step, a pulse voltage is applied by using a pulse power source with a duty ratio, which is a voltage application time per pulse period, set to 5 to 60%.
7. In the vanadium silicocarbide film forming step, the vanadium chloride gas, the silicon source gas, the carbon source gas, the hydrogen gas and the argon gas are supplied into the chamber; 7. The method for producing a vanadium silicocarbide film-coated member according to claim 5, wherein a flow rate ratio of the vanadium chloride gas, the silicon source gas, the carbon source gas, the hydrogen gas and the argon gas is 1:0.25-2:3-20:20-35:0.5-2.
8. The method for producing a vanadium silicocarbide film-coated member according to any one of claims 5 to 7, wherein the silicon source gas is an organosilane gas.
9. 9. The method for producing a vanadium silicocarbide film-coated member according to claim 8, wherein the organosilane gas is monomethylsilane gas.
Citation Information
Patent Citations
Hard film excellent in wear resistance and oxidation resistance and high hardness member
JP1995300649A
Discharge surface treatment method, and treatment device
JP1998225824A
Vanadium silicide carbide nitride film, member covering vanadium silicide carbide nitride film and method for manufacturing the same
JP2019035108A